Wall construction / Nazrul Ikwan Ismail - Ismail, Nazrul Ikwan (Universiti Teknologi Mara, Perak, 2014)
This report briefly describes the processes and methods involved in the construction of the wall. It is produced based on the experience of the past five months stationed at the project site. This report is divided into sections and start with the background and the background of the construction project. The observation found that the construction of the wall is not as easy as it looks. It involves many parties and the construction process very complex. In this report, briefly described the types and the main components of a wall. Then described in more detail about the methods involved and used in wall construction includes construction process binding bricks, plaster, followed by finishing work such as wall paint, tile, and shera. During the process of roof construction is underway, some of the problems associated with the method of wall construction nationwide have been identified. The report is able to explain in more detail the process and practical method of wall construction to readers. The report describes the processes and methods involved in the construction of wall. The construction of the wall is not as easy as it can be seen. It involved many complex stages in the construction process. Finally, his report explain the construction of materials used together with the construction of a brick tie and followed by wall finishes.